2021
DOI: 10.1021/acs.est.0c08621
|View full text |Cite
|
Sign up to set email alerts
|

Does Arsenic Contamination Affect DNA Methylation Patterns in a Wild Bird Population? An Experimental Approach

Abstract: Pollutants, such as toxic metals, negatively influence organismal health and performance, even leading to population collapses. Studies in model organisms have shown that epigenetic marks, such as DNA methylation, can be modulated by various environmental factors, including pollutants, influencing gene expression, and various organismal traits. Yet experimental data on the effects of pollution on DNA methylation from wild animal populations are largely lacking. We here experimentally investigated for the first… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…DNA methylation is especially prone to changes during early life. In vertebrates, DNA methylation is reported to be affected during early life by temperature ( Sheldon et al 2020 ), the type of rearing environment ( Morán et al 2013 ; Venney et al 2021 ), brood size ( Sheldon et al 2018 ; Sepers et al 2021 ), parental care ( Weaver et al 2004 ), nutrition ( Waterland and Jirtle 2003 ; Sandovici et al 2011 ), and pollutant exposure ( Laine et al 2021 ; Mäkinen et al 2022 ). Thus, methylation marks can either be highly programmed and differ little in state between individuals or be influenced by a combination of genetic and environmental factors that lead to inter- and intraindividual variation in DNA methylation states.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is especially prone to changes during early life. In vertebrates, DNA methylation is reported to be affected during early life by temperature ( Sheldon et al 2020 ), the type of rearing environment ( Morán et al 2013 ; Venney et al 2021 ), brood size ( Sheldon et al 2018 ; Sepers et al 2021 ), parental care ( Weaver et al 2004 ), nutrition ( Waterland and Jirtle 2003 ; Sandovici et al 2011 ), and pollutant exposure ( Laine et al 2021 ; Mäkinen et al 2022 ). Thus, methylation marks can either be highly programmed and differ little in state between individuals or be influenced by a combination of genetic and environmental factors that lead to inter- and intraindividual variation in DNA methylation states.…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies have attempted to reveal the toxicity of arsenic to human, especially trivalent inorganic arsenic. Inorganic arsenic and its compounds were generally considered to be more toxic than organic arsenic. Modern studies have shown that exposure to inorganic arsenic could lead to DNA damage and protein denaturation. Although many research studies aimed at revealing the mechanism of arsenic damage to body, early detection of arsenic exposure at low doses was still difficult. When clinical symptoms of arsenic exposure have occurred, the body has usually already suffered some serious damage.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies reported that As, Cd, Co, Cr, Cu, Pb, Ni and Zn have remarkable impacts on avian communities; for example, an excessive level of As can damage the DNA in birds [26]. A higher level of Cd in birds can damage their flying mechanisms and lead to poor development of bones [27].…”
Section: Introductionmentioning
confidence: 99%